DESIGN AND DEVELOPMENT OF THE MEASURING OF THE BODY MASS INDEX TO THE INDONESIA NAVY BASED ON VISUAL STUDIO - Zainal Syahlan; Depilia Surya Candra; Edy Widodo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Height and weight measurement tools are one of the important measurement tools used to monitorthe health status of the Navy personnel periodically every six months through the URIKES program, witha comparison between height and weight later this will be known to the health status of soldiers in theunderweight category , Normal, Overweight and Obesity. With this monitored health status, it is hopedthat Indonesian Navy soldiers will not be constrained by health problems in carrying out their duties ortraining and can assist leaders in determining policies. In this final project, a system will be designed tomake it easier and faster to measure height and weight automatically using the Sharp sensor as a heightgauge and the Load Cell sensor as a weight gauge. The output of this measuring device is in the form ofdisplay on a PC monitor and can be uploaded then the data can be stored on the server, so it can beaccessed via Android. This tool is expected to later be used as a substitute for measuring height andweight that is still manual.Keywords: URIKES, underweight, Normal, Overweight, Obesity, Sharp Sensor, Load Cell Sensor andAndroid.